A Study of The Perceptions of Trawl Fishermen Towards The Rules of The Trawl Ban on The North Coast of East Java - M Iqbal Satria; Adriana Monica Sahidu; Gunanti Mahasri; Fuad (Universitas Islam Lamongan, 2024)
The issuance of the cantrang prohibition regulation, namely Permen Kp No. 2 of 2015, is based on the decline in Fish Resources (SDI) which threatens sustainability, so for the sake of sustainability it is necessary to impose a ban on the use of trawls and seine nets including cantrang. This study will analyze how the perception of the seine net fishing community towards the rules of the cantrang ban. This study used survey methods, questionnaires and interviews and was conducted at PPP Mayangan Probolinggo and PPP Bulu Tuban. The number of samples in this study were 20 respondents with purposive sampling. Data analysis using Likert scale, validity test and reliability test. The results showed that if the government emphasizes the rules of the cantrang ban, cantrang fishermen will really lose income, causing increased unemployment, especially for crew members. On the other hand, the Ministerial Regulation will have a positive impact for the future in the form of sustainability of marine fish resources.